Mimesis – wyróżniki i formy twórczości poetyckiej według Arystotelesa - Wesoły, Marian Andrzej (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2022)
This article concerns the first six chapters of Aristotle’s Poetics within the Greek text provided. The introductory note is intended to prepare the reader for an integrated approach to the issues stated in the title. We propose a new Polish translation of this text in a rendition as close to the original as possible. For the sake of clarity, we highlight the chapters with various appropriate thematic headings. In contrast to most translations and commentaries, we show Aristotle speaking of forms (eide), not in the sense of literary genres or species but in the sense of forms as components (mere) of mimesis under the triad of complementary distinctions, which are the means, the objects and the modes of poetic imitation.